Highly active self-assembled hybrid catalyst with multiphase heterointerfaces to accelerate cathodic oxygen reduction of intermediate-temperature solid oxide fuel cells. Issue 7 (May 2020) - Yang, Yang; Li, Ruoyu; Wu, Yujie; Chu, Yuting; Tian, Dong; Lu, Xiaoyong; Guo, Litong; Lin, Bin; Feng, Peizhong; Ling, Yihan
Abstract: Exploring highly active cathode materials with fast cathodic oxygen reduction has been considered as one of the most promising approaches to accelerate the commercialization process of intermediate temperature solid oxide fuel cells (IT -SOFCs). Herein, a highly active hybrid catalyst system with multiphase heterointerfaces consisting of (PrSr)Ni0.5 Mn0.5 O3-δ, PrOx nanoparticles and (PrSr)2 (MnNi)O4-δ is self-assembly formed by substitution of Sr into Pr2 Ni0.5 Mn0.5 O4-δ (S-PNM). Further using S-PNM as cathode materials for IT-SOFCs, S-PNM achieves a remarkable maximum power density of 960 mW cm −2 at 800 °C and an outstanding short-term stability with the discharge voltage of 0.68 V for 80 h. The excellent electrochemical performance by the preliminary experimental results is attributed to the coexistence of multiphase heterointerfaces of (PrSr)Ni0.5 Mn0.5 O3-δ, (PrSr)2 (MnNi)O4-δ and PrOx nanoparticles, which can accelerate cathodic oxygen reduction.